The Integration of Faith and Piety and Science and Technology on Arabic Learning Process: Case Study at Darul Ulum Islamic University Banyuanyar Pamekasan - Hamdy, Mohammad Zainal; Huda, Miftahul (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2023)
Dichotomy is a scourge for the development of science and technology in Islamic education, the West claims superiority as the legitimate owner of the development of science and technology with its arrogance, while Islam seems to be asleep and hypnotized by it, even though Islam is the initial mover of the development of science and technology with real historical evidence. STAI DUBA Pamekasan tries to make people aware that in Islamic education the integration of imtaq and science and technology can be realized and the dichotomy between the two must be immediately eradicated. This research will explain how the process of integration of imtaq and science and technology at STAI DUBA Pamekasan and what are the supports and obstacles. This study uses qualitative research with the type of field. The result is that the process of integration of imtaq and science and technology at STAI DUBA Pamekasan takes place not only in the room, it also takes place in all educational activities under STAI DUBA Pamekasan